2018
DOI: 10.3389/fmars.2018.00411
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Sea Turtle Mortality Events in El Salvador Attributed to Paralytic Shellfish Toxin-Producing Algae Blooms

Abstract: In late October and early November 2013 and 2017, hundreds of sea turtles were found dead along the Pacific coastline of El Salvador. The dead turtles were in good body condition and did not have any injuries or other major anomalies. In order to determine the role of paralytic shellfish toxins (PST) in this mass mortality, tissue samples, including blood, flipper, liver, kidney, stomach and intestinal contents, of dead green turtles (Chelonia mydas) and olive ridley turtles (Lepidochelys olivacea) were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
9
0
3
Order By: Relevance
“…Harmful Algal Blooms (HABs) are proliferations of phytoplankton (mostly dinoflagellates, diatoms and cyanobacteria) and macroaglae that have negative effects on marine environments and associated biota. Impacts include water discolouration and foam accumulation, anoxia, contamination of seafood with toxins, disruption of food webs and massive large-scale mortality of marine biota (Hallegraeff, 2010;Quillien et al 2015;Amaya et al 2018;García-Mendoza et al 2018;Álvarez et al 2019). The IPCC 5th Assessment Report (AR5) concluded that harmful algal outbreaks had increased in frequency and intensity, caused partly by warming, nutrient fluctuations in upwelling areas, and coastal eutrophication (medium confidence); however, there was limited evidence and low confidence for future climate change effects on HABs (AR5 Chapters 5, 6) (Pörtner et al 2014;Wong et al 2014b).…”
Section: Box 54 | Harmful Algal Blooms and Climate Changementioning
confidence: 99%
“…Harmful Algal Blooms (HABs) are proliferations of phytoplankton (mostly dinoflagellates, diatoms and cyanobacteria) and macroaglae that have negative effects on marine environments and associated biota. Impacts include water discolouration and foam accumulation, anoxia, contamination of seafood with toxins, disruption of food webs and massive large-scale mortality of marine biota (Hallegraeff, 2010;Quillien et al 2015;Amaya et al 2018;García-Mendoza et al 2018;Álvarez et al 2019). The IPCC 5th Assessment Report (AR5) concluded that harmful algal outbreaks had increased in frequency and intensity, caused partly by warming, nutrient fluctuations in upwelling areas, and coastal eutrophication (medium confidence); however, there was limited evidence and low confidence for future climate change effects on HABs (AR5 Chapters 5, 6) (Pörtner et al 2014;Wong et al 2014b).…”
Section: Box 54 | Harmful Algal Blooms and Climate Changementioning
confidence: 99%
“…Toxin concentrations were lower in gastric contents than whole fish, which could reflect degradation or absorption. Sea turtle mortality associated with STX-producing dinoflagellate blooms is reported from the Pacific coast of Mexico and Central America, and Papua New Guinea (14)(15)(16)(17). These published accounts reported higher STX toxin concentrations in individual turtle tissues (1.16-4.78 µg STX eq/g) than STXs we detected in green turtles feeding on C. rostrata (approximately 0.04 µg STXs/g).…”
Section: Discussionmentioning
confidence: 54%
“…Saxitoxins were recorded in different organs and gastric contents of the turtles up to 1616 µg SXT eq.100 g -1 of tissue, as well as Pyrodinium cells in their digestive tract. However, Pbc was not registered in the water column or it was extremely scarce (20 cells l -1 ) (Amaya et al, 2018).…”
Section: Pyrodinium Bahamense Var Compressummentioning
confidence: 94%